2011
DOI: 10.1038/aps.2011.52
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein promotes hepatoma cell proliferation via upregulation of MEKK2

Abstract: Aim: To investigate the mechanism underlying the increase of hepatoma cell proliferation by hepatitis B virus X protein (HBx). Methods: HepG2, H7402 and HepG2.2.15 cells, which constitutively replicated hepatitis B virus were used. The effects of HBx on hepatoma cell proliferation were examined using 5-ethynyl-2-deoxyuridine (EdU) incorporation assay and MTT assay. The expression level of MEKK2 was measured using RT-PCR, Western blot and luciferase reporter gene assay. The activity of activator protein 1 (AP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…Previous studies have shown that HBx induces cell proliferation of the HCC cells [7], [13], [24]. Although, HBx induces proliferation via several mechanisms, very limited data is available on the role of HBx-induced miRNAs in regulating the proliferation and metastasis in HCC [9], [14], [18].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that HBx induces cell proliferation of the HCC cells [7], [13], [24]. Although, HBx induces proliferation via several mechanisms, very limited data is available on the role of HBx-induced miRNAs in regulating the proliferation and metastasis in HCC [9], [14], [18].…”
Section: Resultsmentioning
confidence: 99%
“…HBV DNA was exclusively integrated into the genome of the HBVassociated HCC tumor tissues in individuals who were positive for the HBX transcript but negative for the HBV surface antigen (HBsAg), thereby suggesting the role of HBV in genome integration and malignancy transformation [12]. Several studies showed that HBX can promote proliferation, motility and invasion in human hepatocytes by up-regulating MEKK2, MIG, MMP-9, IKKa and Capn4 [13][14][15][16][17]. HBX has also been shown to be involved in controlling tumor growth via modifying cell cycle progression by regulating cell cycle regulatory protein in a calcium-dependent manner [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…HBx has been shown to induce various signaling pathways and cellular proteins that could link HCC with HBV infection (31)(32)(33). Studies have shown that HBx protein induces the expression of oncogenic miR-21, but the molecular mechanism of the role of miR-21 in HBx-induced proliferation and apoptosis in HCC cells is still unknown.…”
Section: Discussionmentioning
confidence: 99%